A scoping review of trauma-informed care principles applied in design and technology - Melissa Eggleston; Emily P Jones; Nashmia Khan; William A Romani; Kyle McQuillan; Jessica Otero; Elizabeth Chen (Digital Health, 2025)
Objectives Since psychological trauma and the use of technology are common in society, designers and researchers have been applying a trauma-informed (TI) approach to the digital design of technology. A TI approach was developed by the social work field to better serve those who have been through trauma. The purpose of this scoping review was to determine the current state of scholarly research on TI digital design and technology. Methods Searches were conducted in five databases for peer-reviewed articles about the design of digital interventions using TI approaches, published from 2000 to 2023. One hundred and eighteen studies were included and examined for their use of TI approaches, settings, types of digital design, and types of organizations and practitioners designing. Results Studies and interventions are not explicitly or methodically applying a TI approach to digital design, despite hopes to serve populations with significant trauma (e.g., life-threatening cancer survivors) in various settings. Efforts are sometimes consciously made that align with TI principles (e.g., safety), but other times there's no accounting for trauma and its impacts in the design of interventions. Conclusion The review indicates that there is a lack of using the evidence-based framework of a TI approach in digital design.